Internal and external training load associations in professional soccer players - Clemente, F. M. (Journal of Human Sport & Exercise, 2019)
The purpose of this study was to test the correlation levels between internal load (perceived exertion - RPE; session-RPE) and external load (total [TD], running [RD] and sprinting [SD] distances, and player load [PL]) measures. The study monitored 23 professional soccer players (24.9±3.5 years old; height: 168.8±41.4 cm; body mass: 71.6±18.7 kg) from a team competing in the first Portuguese league. The players were monitored daily for internal and external load measures over a one-month period. Very large positive correlations between RPE and the external load measures of TD (r=0.84), RD (r=0.79), SD (r=0.73). and PL (r=0.90) were found. Correlation levels between session-RPE and TD (r=0.74), RD (r=0.77), and PL (r=0.79) were positive and very large. The evidence of the present study suggests that RPE and session-RPE are valid methods for estimating the overall load exerted by players during matches and training sessions. This can be very important, especially for teams without the economic resources required to monitor RPE using objective measurement instruments.